Probing aqueous ions with non-local Auger relaxation. Issue 15 (31st March 2022) - Gopakumar, Geethanjali; Muchová, Eva; Unger, Isaak; Malerz, Sebastian; Trinter, Florian; Öhrwall, Gunnar; Lipparini, Filippo; Mennucci, Benedetta; Céolin, Denis; Caleman, Carl; Wilkinson, Iain; Winter, Bernd; et al.
Abstract : Non-local analogues of Auger decay, such as Intermolecular Coulombic Decay, are increasingly recognized as important relaxation processes in aqueous electrolytes. Abstract : Non-local analogues of Auger decay are increasingly recognized as important relaxation processes in the condensed phase. Here, we explore non-local autoionization, specifically Intermolecular Coulombic Decay (ICD), of a series of aqueous-phase isoelectronic cations following 1s core-level ionization. In particular, we focus on Na +, Mg 2+, and Al 3+ ions. We unambiguously identify the ICD contribution to the K-edge Auger spectrum. The different strength of the ion–water interactions is manifested by varying intensities of the respective signals: the ICD signal intensity is greatest for the Al 3+ case, weaker for Mg 2+, and absent for weakly-solvent-bound Na + . With the assistance of ab initio calculations and molecular dynamics simulations, we provide a microscopic understanding of the non-local decay processes. We assign the ICD signals to decay processes ending in two-hole states, delocalized between the central ion and neighbouring water. Importantly, these processes are shown to be highly selective with respect to the promoted water solvent ionization channels. Furthermore, using a core-hole-clock analysis, the associated ICD timescales are estimated to be around 76 fs for Mg 2+ and 34 fs for Al 3+ . Building on these results, we argue that Auger and ICD spectroscopy represents a unique tool for the exploration of intra- and inter-molecular structure in the liquid phase, simultaneously providing both structural and electronic information.